Relaciones entre la historia de la filosofía y la filología con base en el libro Plauto y Descartes - Lafuente, María Isabel (Estudios humanísticos. Historia, 2011)
In this paper the relations between History of the Philosophy and Philology are analyzed starting from the consideration of the work of Descartes as a reproduction of the schemes of Plauto's theatre. It is shown that it is impossible to reduce this philosophy to its philological sources, as well as the ways of considering the sources, the problems that it involves, and how to understand Humanism in Cartesian philosophy.